Update on Intra-Arterial Chemotherapy for Retinoblastoma - Mario Zanaty; Guilherme Barros; Nohra Chalouhi; Robert M. Starke; Philip Manasseh; Stavropoula I. Tjoumakaris; Carol L. Shields; David Hasan; Ketan Bulsara; Robert H. Rosenwasser; Pascal Jabbour (The Scientific World Journal)
The tools for managing retinoblastoma have been increasing in the past decade. While globe-salvage still relies heavily on intravenous chemotherapy, tumors in advanced stage that failed chemotherapy are now referred for intra-arterial chemotherapy (IAC) to avoid enucleation. However, IAC still has many obstacles to overcome. We present an update on the indications, complications, limitations, success, and technical aspects of IAC. Given its safety and high efficacy, it is expected that IAC will replace conventional strategies and will become a first-line option even for tumors that are amenable for other strategies.